Over-the-counter carrageenan-based sprays may interfere with PCR testing of nasopharyngeal swabs to detect SARS-CoV-2 - Taylor Corocher; Kira Edwards; Yvonne Hersusianto; Donald Campbell; Hui Yin Lim; Paul Monagle; Prahlad Ho (PLoS ONE, 2025)
Carrageenan-containing nasal sprays, available over-the-counter (OTC), are often marketed as having anti-viral effects. Carrageenan belongs to the glycosaminoglycan family alongside heparin, and heparin is known to inhibit real-time quantitative polymerase chain reaction (RT-qPCR) in nasopharyngeal swabs used to detect SARS-CoV-2. As heparin and carrageenan share structural similarities, this work aimed to investigate the interferent effect of carrageenan on RT-qPCR for SARS-CoV-2 detection across 4 different diagnostic platforms. This work demonstrated that in the presence of carrageenan samples return inaccurate and invalid results on the Seegene STARlet, while qualitative accuracy was maintained on the Cepheid GeneXpert, Roche Cobas LIAT, and Hologic Panther Aptima. Evidence of carrageenan interference on SARS-CoV-2 testing was consistent across two OTC brands and research-grade reconstituted iota-carrageenan, with 80% of results returning invalid regardless of the carrageenan formulation added to the samples. Further, a preliminary in vivo interference study demonstrated an increased Ct value within 15 minutes of carrageenan dosage, with Ct values restored 60 minutes post-application. A direct comparison of carrageenan- and heparin-mediated PCR interference demonstrated that carrageenan PCR interference occurs to a lesser degree, but is not reversible by the addition of heparinase I. As carrageenan is available OTC, interference with PCR testing that causes an increase in false negative results could lead to accidental spread of disease and could therefore have significant public health impacts on community testing of respiratory infectious diseases via PCR.